Training EFL teachers online: how to improve results among adult learners (based on the experiment in Skyeng School) - N. S. Berezin (Дискурс профессиональной коммуникации, 2020)
The paper considers the organizational aspect of EFL teachers’ professional development with a view to improving the educational results of their students. The author suggests a way of determination of the necessity for professional development, a way to organize the process of professional development and the means of measuring the effectiveness of this process. The fundamental didactic principle of the proposed approach is the timely on-the-job professional teacher`s development. At the beginning of the paper, the author discusses the changes that came along with the development of the EdTech market, online tools in education, opening up both new requirements and new opportunities to solve the problems of all participants of the educational process. Among the burning problems of the participants of the educational process are the following ones: the individual educational request of the student, the requirements of companies for the competencies of employees and candidates in the market, the influence on the student's result by the teacher’s training, the automation of teaching aids and tools for their analysis. One of the main demands of our time is, surely, the development of separate competencies, such as: social, emotional and digital activities of a person, the ability to be flexible in relation to circumstances, the ability to learn and relearn. The ecosystem solution of the listed problems is considered by the author as the most effective way, which is designed not to separate, but to unite the efforts that coordinate the goals of each of the participants and satisfy their needs. It is proposed to influence the student's result, formulated by themselves in accordance with the market or individual educational needs, by providing teachers with timely training and support for conducting a good first and subsequent lessons. As the evidence of the effectiveness of the considered approach, the main part of the article views the experiment of the training center team responsible for the training of 10,000+ English teachers at the Skyeng online school. This part provides an exhaustive description of the project, the proposed tools, training formats and metrics to calculate the effectiveness of the experiment; for the purpose of clarity, charts and other visual decryptions are added. The paper ends with a glossary, which will be useful to all experts experimenting in education, but especially for teachers, methodologists and managers of educational programs.